Pengaruh Pemanfaatan Sistem Informasi Akuntansi Keuangan Daerah dan Peran Internal Audit terhadap Kualitas Laporan Keuangan Pemerintah Daerah - Arif Ikbal Arif Ikbal; Budi Safatul Budi; Zulkifli Umar Umar (BE-HISZ : Journal of Economics and Accounting, 2025)
This study aims to examine the effect of the utilization of regional financial accounting information systems and the role of internal audit on the quality of local government financial statements. A quantitative research approach was employed, with the study conducted at the Housing and Settlement Office (Perumahan dan Permukiman/Perkim) of Aceh Province. Primary data were collected through a structured questionnaire distributed to 25 employees directly involved in regional financial management. The data were analyzed using multiple linear regression with the assistance of Statistical Package for Social Science (SPSS). The results indicate that the utilization of regional financial accounting information systems and the role of internal audit simultaneously have a significant effect on the quality of local government financial statements. Furthermore, partial testing reveals that each independent variable has a positive and significant influence on financial reporting quality. These findings suggest that the effective use of integrated financial accounting information systems, supported by adequate information technology infrastructure, along with a strong and independent internal audit function, plays a crucial role in enhancing the relevance, reliability, comparability, and understandability of local government financial statements. This study provides practical implications for local governments to strengthen the implementation of regional financial accounting information systems and reinforce the internal audit function to improve transparency and accountability in public financial management. In addition, the findings contribute to the existing literature and may serve as a reference for future studies by expanding research objects and variables.